2007
DOI: 10.1093/jxb/erm080
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis enhanced ethylene response 4 encodes an EIN3-interacting TFIID transcription factor required for proper ethylene response, including ERF1 induction

Abstract: eer4 was isolated as an Arabidopsis mutant with an extreme response to ethylene in dark-grown seedlings that was also found to have partial ethylene insensitivity at the level of ethylene-dependent gene expression, including ERF1. Subsequent cloning of eer4 revealed an inappropriate stop codon in a previously uncharacterized TFIID-interacting transcription factor homologous to human TAF12 and yeast TAF61. Genetic and pharmacological analysis demonstrated that the eer4 phenotype is strictly ethylene dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…4B). It was found that sar1-7 significantly restored ethylene-dependent hypocotyl shortening to an ein3-1 background, with the sar1-7 mutation probably resulting in amplification of the limited amount of ethylene signalling that still occurs in ein3-1 (Chao et al , 1997), similar to that seen for other eer mutants (Christians et al , 2008; Robles et al , 2007). In conjunction with the increased ethylene responsiveness of ein3-1 / sar1-7 hypocotyls, ethylene treatment resulted in presentation of a full apical hook in ein3-1 / sar1-7 in contrast to ein3-1 , which was incapable of ethylene-dependent exaggerated apical hook formation.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…4B). It was found that sar1-7 significantly restored ethylene-dependent hypocotyl shortening to an ein3-1 background, with the sar1-7 mutation probably resulting in amplification of the limited amount of ethylene signalling that still occurs in ein3-1 (Chao et al , 1997), similar to that seen for other eer mutants (Christians et al , 2008; Robles et al , 2007). In conjunction with the increased ethylene responsiveness of ein3-1 / sar1-7 hypocotyls, ethylene treatment resulted in presentation of a full apical hook in ein3-1 / sar1-7 in contrast to ein3-1 , which was incapable of ethylene-dependent exaggerated apical hook formation.…”
Section: Resultsmentioning
confidence: 53%
“…7A–C, whereas there was only a slight difference in hypocotyl length when comparing the AgNO 3 control with AgNO 3 +IAA, there was a severe reduction in hypocotyl length for seedlings treated with both saturating ethylene and IAA compared with treatment with ethylene alone. The phenotype of seedlings that were treated with a combination of saturating ethylene and IAA was indistinguishable from the phenotypes of several published eer mutants including eer1 / rcn1 , eer3 , and eer5 (Larsen and Cancel, 2003; Christians and Larsen, 2007; Robles et al , 2007; Christians et al , 2008). …”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Additional transcriptional regulation of ethyleneresponsive genes downstream of or in concert with EIN3 is not unprecedented. EER4, which encodes a TFIID-interacting transcription factor, is required for the accurate induction of ERF1 transcript and thus is important for the canonical ethylene response (Robles et al, 2007). We have shown that ethylene-regulated genes are misregulated in xct mutants ( Fig.…”
Section: Xct Function May Be Linked To Transcriptional Regulationmentioning
confidence: 85%
“…Ethylene response mutants include the constitutive triple response mutants constitutive triple response1 (ctr1), ethylene overproducer1 (eto1), eto2, and eto3 as well as the ethylene-insensitive mutants ethylene response1 (etr1), etr2, ethylene insensitive2 (ein2), ein3, ein4, ein5, ein6, and ein7 (Kieber et al, 1993;Guo and Ecker, 2004). In addition to these, mutants with an enhanced ethylene sensitivity have been isolated, including EIN3-binding F-box protein1 (ebf1), ebf2, enhanced ethylene response1 (eer1), eer3, eer4, eer5, and reversion-toethylene sensitivity1 (rte1; Larsen and Chang, 2001;Guo and Ecker, 2003;Resnick et al, 2006;Christians and Larsen, 2007;Robles et al, 2007;Christians et al, 2008). Epistasis and molecular analyses of mutants have revealed a linear ethylene signaling pathway and the core components involved in ethylene perception, signal cascading, and transcriptional regulation Chen et al, 2005).…”
mentioning
confidence: 99%